Silicon-carbon composite material, preparation method and application thereof, and electrochemical device
By calcining soda earth metal and silicon powder under an inert atmosphere and solvothermal reaction with liquid aromatic halogenated hydrocarbons, a small-sized silicon nanomaterial coated with carbon is solved, and the preparation of nano-silicon carbon composites is achieved with low-cost and high-performance silicon-carbon composite materials.
Patent Information
- Application Number
- CN202411852920.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-16
AI Technical Summary
The existing nano-silicon-carbon composite materials have high preparation costs and poor electrochemical performance, making it difficult to meet the needs of low-cost production applications.
The metal silicon precursor is prepared by calcining soda earth metal and silicon powder under an inert atmosphere and undergoing solvothermal reaction with liquid aromatic halogenated hydrocarbons to form a carbon-coated small-sized silicon nanomaterial, and the reaction activity of the metal silicon precursor is adjusted to catalyze dehalogenation and polymerization to form amorphous carbon and nanosilicon particles.
The low-cost preparation of silicon-carbon composite materials is achieved, which improves the conductivity and cycle life of the material, enhances the rate performance and reduces capacity attenuation.
Smart Images

Figure CN119725441A_ABST
Abstract
Description
Technical Field
[0001] The present invention specifically relates to a silicon-carbon composite material and a preparation method, application and electrochemical device thereof. Background Art
[0002] Silicon-based negative electrode materials have extremely high research value and application prospects in the field of lithium-ion batteries. Their theoretical specific capacity is as high as 4200mAh / g. Compared with traditional graphite negative electrodes, silicon-based negative electrodes can achieve higher endurance in lithium-ion batteries. However, in practical applications, due to the significant volume expansion of silicon-based negative electrodes during the charging and discharging process, this expansion will lead to pulverization of electrode materials, destruction of electrode structure, and repeated formation of solid electrolyte interface (SEI) films. These problems seriously affect the cycle performance of the battery. Therefore, the potential of silicon-based negative electrodes has not been fully utilized, and their use ratio in batteries is often difficult to exceed 10%. In order to solve this problem, researchers mainly use nano-silicon technology to improve the performance of silicon negative electrodes.
[0003] Nano silicon can alleviate the stress caused by volume expansion to a certain extent due to its unique size effect. Many studies have shown that by combining nano silicon with carbon materials, the electrochemical properties of nano silicon negative electrode materials such as conductivity and cyclability can be improved. However, the preparation cost of nano silicon carbon negative electrode materials is relatively high, and they rely on equipment such as sand mills, chemical vapor deposition equipment or carbonization furnaces to complete silicon nano-sizing and carbon coating respectively, which is difficult to meet the needs of low-cost production applications. Summary of the invention
[0004] The technical problem solved by the present invention is to overcome the problems of high preparation cost and poor electrochemical performance of nano silicon-carbon composite materials in the prior art, and provide a silicon-carbon composite material and its preparation method, application and electrochemical device. The silicon-carbon composite material prepared by the present invention has good conductivity and cycle life; and the preparation method is simple, low-cost and can be produced by industrialization.
[0005] The present invention firstly adopts alkaline earth metal and silicon powder to prepare a metallic silicon precursor, so that silicon atoms are uniformly dispersed in the alkaline earth metal; then the metallic silicon precursor is subjected to a solvent thermal reaction with liquid aromatic halogenated hydrocarbons. During the solvent thermal reaction, the alkaline earth metal in the metallic silicon precursor catalyzes the dehalogenation of the aromatic halogenated hydrocarbons. During the dehalogenation, planar and spatial polymerization of the benzene rings occurs to form amorphous carbon, and the silicon in the metallic silicon precursor further forms nano silicon particles at a relatively low temperature, thereby forming a carbon-coated small-sized silicon nanomaterial, and the alkaline earth metal in the metallic silicon precursor generates an alkali metal salt with the halogen; the carbon material coated on the surface of the nano silicon can uniformly disperse and fix the nano silicon particles to prevent them from agglomerating, inhibit the expansion of silicon during the charge and discharge process, and provide a three-dimensional conductive network, thereby improving the rate performance and reducing the capacity attenuation.
[0006] The present invention solves the above technical problems through the following technical solutions:
[0007] The present invention provides a method for preparing a silicon-carbon composite material, which comprises the following steps:
[0008] (1) Under an inert atmosphere, calcining a mixture of alkaline earth metal and silicon powder at 300-800° C. for 2-8 hours to prepare a metallic silicon precursor;
[0009] (2) subjecting the metallic silicon precursor and a mixture of liquid aromatic halogenated hydrocarbons to a solvothermal reaction to obtain the silicon-carbon composite material; the mass ratio of the metallic silicon precursor to the liquid aromatic halogenated hydrocarbon is 1:(1-20).
[0010] In the present invention, the inert atmosphere may be any conventional gas in the art, generally referring to a gas that does not react with the reactants, such as nitrogen, argon or helium.
[0011] In the present invention, the alkaline earth metal may be one or more of Mg, Ca, Sr and Ba, preferably Ca and / or Mg.
[0012] In the present invention, the size of the silicon powder may be 10 nm-2 μm.
[0013] In the present invention, the molar ratio of the alkaline earth metal to the silicon powder may be 4:(1.5-8), preferably 4:(1.5-2), for example 4:1.8, 4:1.85, 4:1.9, 4:1.95 or 4:2.
[0014] In some embodiments, the alkaline earth metals are Mg and Ca, and the molar ratio of Mg to Ca may be (1-4):1, preferably (2-4):1, such as 3:1.
[0015] In some embodiments, the alkaline earth metal is Mg and Ca, and the molar ratio of Mg:Ca:silicon powder can be (1-4):1:(1.5-2), such as 3:1:1.8, 3:1:1.9 or 3:1:2. The chemical reactivity can be adjusted by adjusting the composition and ratio of the alkaline earth metal and silicon.
[0016] In the present invention, the calcination is generally carried out in a tube furnace.
[0017] In the present invention, the rate of heating to the calcination temperature may be 2-5°C / min.
[0018] In the present invention, the calcination temperature is preferably 400-600°C, such as 500°C.
[0019] In the present invention, the calcination time is preferably 3-6 hours, such as 4 hours or 5 hours.
[0020] In the present invention, the chemical formula of the metal silicon precursor can be Ca 4-x Mg x Si2, wherein 0≤x≤4, for example, x is 0.5, 1, 2 or 4.
[0021] In the present invention, the liquid aromatic halogenated hydrocarbon generally refers to one or more hydrogen atoms in an aromatic hydrocarbon molecule replaced by a halogen atom. The halogen in the liquid aromatic halogenated hydrocarbon may be one or more of F, Cl, Br and I, such as Cl. The number of halogen atoms in the liquid aromatic halogenated hydrocarbon may be 1-6, such as 1, 2 or 3. The liquid aromatic halogenated hydrocarbon may be a liquid side chain halogenated aromatic hydrocarbon and / or a liquid aromatic ring halogenated aromatic hydrocarbon. The halogen in the liquid side chain halogenated aromatic hydrocarbon is preferably a halogenated aromatic hydrocarbon connected to the α position of the side chain, such as benzyl chloride. The liquid aromatic ring halogenated aromatic hydrocarbon may be one or more of chlorobenzene, 2,6-dichlorotoluene, 1,2-dichlorobenzene and p-chlorotoluene.
[0022] In the present invention, the mass ratio of the metal silicon precursor to the liquid aromatic halogenated hydrocarbon is, for example, 1:1, 1:2, 1:3, 1:5 or 1:10, preferably 1:(8-15).
[0023] In the present invention, the solvothermal reaction generally refers to a synthesis method in which the original mixture reacts in a closed system with an organic solvent or a non-aqueous solvent as a solvent at a certain temperature and autogenous pressure of the solution. The solvothermal reaction is generally carried out in a reaction kettle.
[0024] In the present invention, the rate of heating to the temperature of the solvothermal reaction may be 1-5°C / min.
[0025] In the present invention, the temperature of the solvothermal reaction generally does not exceed the boiling point of the liquid aromatic halogenated hydrocarbon, and is preferably 80-160°C, such as 85°C, 100°C, 120°C or 150°C, and more preferably 100-160°C.
[0026] In some embodiments, when the liquid aromatic halogenated hydrocarbon is chlorobenzene, the temperature of the solvothermal reaction is preferably 80-120°C, such as 85°C or 120°C, more preferably 100-120°C.
[0027] In some embodiments, when the liquid aromatic halogenated hydrocarbon is 2,6-dichlorotoluene, the temperature of the solvothermal reaction is preferably 100-160°C, such as 120°C or 150°C, more preferably 100-130°C.
[0028] In some embodiments, when the liquid aromatic halogenated hydrocarbon is benzyl chloride, the temperature of the solvothermal reaction is preferably 100-160°C, such as 120°C or 150°C, more preferably 100-130°C.
[0029] In the present invention, the solvent thermal reaction time may be 3-18 h, such as 5 h, 6 h, 8 h or 10 h, preferably 8-12 h.
[0030] In the present invention, according to the conventional art, washing and drying are generally required after the solvent thermal reaction is completed. The solvent used in the washing process can be one or more of DMF, DMSO and NMP, such as DMF.
[0031] The present invention also provides a silicon-carbon composite material prepared by the preparation method as described above.
[0032] The present invention also provides an application of the silicon-carbon composite material as described above in a lithium-ion battery.
[0033] The present invention also provides an electrochemical device, which comprises the silicon-carbon composite material as described above.
[0034] In the present invention, the electrochemical device may be conventional in the art, such as a lithium ion battery.
[0035] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0036] The reagents and raw materials used in the present invention are commercially available.
[0037] The positive and progressive effects of the present invention are:
[0038] The silicon-carbon composite material prepared by the present invention can prepare highly dispersed nano-silicon negative electrode materials uniformly coated with carbon by in-situ catalytic dehalogenation at a relatively low temperature by adjusting the reaction activity of the metallic silicon precursor. The carbon layer can inhibit silicon expansion and agglomeration, greatly improving the cycle life and rate performance of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 is the XRD pattern of the silicon-carbon composite material prepared in Example 1;
[0040] Figure 2 This is a TEM image of the silicon-carbon composite material prepared in Example 1. DETAILED DESCRIPTION
[0041] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0042] The silicon powder used in the following examples and comparative examples was purchased from Aladdin, and had a purity of 99.9% and a particle size of about 1 μm.
[0043] Example 1
[0044] (1) Mixing magnesium powder, calcium powder and silicon powder in a molar ratio of 3:1:1.8 and putting them into a crucible, adding them into a tube furnace, heating them to 500°C at a heating rate of 5°C / min in a nitrogen atmosphere, keeping them for 4 hours and then cooling them naturally to room temperature to obtain a metal silicon precursor;
[0045] (2) The metallic silicon precursor and chlorobenzene (AR) were mixed in a mass ratio of 1:10, heated to 120°C in a reactor at a heating rate of 3°C / min, kept warm for 10 h, cooled to room temperature, washed three times with DMF, and dried to obtain a nano-silicon-carbon composite material.
[0046] Example 2
[0047] Compared with Example 1, except that the molar ratio of metal magnesium powder, metal calcium powder and silicon powder in step (1) is adjusted to 3:1:1.9, the other parameters and conditions are the same as those in Example 1.
[0048] Example 3
[0049] Compared with Example 1, except that the molar ratio of metal magnesium powder, metal calcium powder and silicon powder in step (1) is adjusted to 3:1:2, other parameters and conditions are the same as those in Example 1.
[0050] Example 4
[0051] Compared with Example 1, except that the molar ratio of metal magnesium powder, metal calcium powder and silicon powder in step (1) is adjusted to 0:4:1.8, the other parameters and conditions are the same as those in Example 1.
[0052] Example 5
[0053] Compared with Example 1, except that the mass ratio of the metal silicon precursor to chlorobenzene in step (2) is adjusted to 1:5, the other parameters and conditions are the same as those in Example 1.
[0054] Example 6
[0055] Compared with Example 1, except that the temperature of the solvent thermal reaction in step (2) is adjusted to 85°C, the other parameters and conditions are the same as those in Example 1.
[0056] Example 7
[0057] Compared with Example 1, except that the holding time of the solvent thermal reaction in step (2) is adjusted to 5 h, the other parameters and conditions are the same as those in Example 1.
[0058] Example 8
[0059] Compared with Example 1, except that chlorobenzene in step (2) is replaced by 2,6-dichlorotoluene, the other parameters and conditions are the same as those in Example 1.
[0060] Example 9
[0061] Compared with Example 1, except that chlorobenzene in step (2) is replaced by 2,6-dichlorotoluene and the reaction temperature is adjusted to 150° C., the other parameters and conditions are the same as those in Example 1.
[0062] Example 10
[0063] Compared with Example 1, except that chlorobenzene in step (2) is replaced by benzyl chloride, the other parameters and conditions are the same as those in Example 1.
[0064] Embodiment 11
[0065] Compared with Example 1, except that chlorobenzene in step (2) is replaced by benzyl chloride and the reaction temperature is adjusted to 150° C., the other parameters and conditions are the same as those in Example 1.
[0066] Comparative Example 1
[0067] 300nm silicon powder (the purchased silicon powder was crushed to D using ethanol medium sand mill 50 is 300nm).
[0068] Comparative Example 2
[0069] The nano silicon powder in comparative example 1 was mixed with chlorobenzene (AR) at a mass ratio of 0.11:1, heated to 120°C at a heating rate of 3°C / min in a reactor, kept warm for 10 hours, cooled to room temperature, washed three times with DMF, and dried.
[0070] Effect Example
[0071] (1) Morphology characterization and XRD testing
[0072] Figure 1 is the XRD pattern of the silicon-carbon composite material prepared in Example 1; Figure 2 TEM image of the silicon-carbon composite material prepared in Example 1. Figure 2 It can be seen that in the prepared silicon-carbon composite material, the silicon particles are small in size and have not undergone obvious agglomeration, and a layer of amorphous carbon is coated on the surface of the nano-silicon particles.
[0073] (2) Electrochemical performance test
[0074] The silicon-carbon composite materials prepared in Examples 1-11 and the materials prepared in Comparative Examples 1-2 were subjected to half-cell tests. The test method is: the above-mentioned materials to be tested are uniformly mixed with the binder CMC (sodium carboxymethyl cellulose) and the conductive carbon black in a mass ratio of 85:5:10, adjusted into a slurry, coated on a copper foil with a coating thickness of 100 microns, and dried at 90°C in vacuum for 12 hours to prepare a lithium battery negative electrode sheet. The simulated battery assembly was carried out in an argon-filled glove box, using a 1 mol / L LiPF6 electrolyte (the solvent is EC, EMC and DMC, EC:EMC:DMC=1:1:1 (volume ratio), a polypropylene microporous membrane as a diaphragm, and a metal lithium sheet as a counter electrode. The electrochemical performance test was carried out on a Land CT2001A battery tester at a temperature of 20°C and a charge and discharge voltage range of 0.01 to 1.5V (1C=250mAh g -1 ). The test results are shown in Table 1.
[0075] Table 1
[0076]
[0077] According to the above experimental results, the silicon-carbon composite material prepared by the present invention has excellent specific capacity and cycle life. According to Comparative Examples 1 and 2, when only silicon powder is used or silicon powder is directly subjected to solvent thermal reaction with chlorobenzene, the first charge specific capacity and the energy retention rate after 500 cycles are poor, especially the cycle capacity retention rate is low.
[0078] Although the specific embodiments of the present invention are described above, it should be understood by those skilled in the art that this is only for illustration and the protection scope of the present invention is defined by the appended claims. Those skilled in the art may make various changes or modifications to these embodiments without departing from the principles and essence of the present invention, but these changes and modifications all fall within the protection scope of the present invention.
Claims
1. A method for preparing a silicon-carbon composite material, characterized in that: The following steps are involved: (1) Under an inert atmosphere, calcining a mixture of alkaline earth metal and silicon powder at 300-800° C. for 2-8 hours to prepare a metallic silicon precursor; (2) subjecting the metallic silicon precursor and a mixture of liquid aromatic halogenated hydrocarbons to a solvothermal reaction to obtain the silicon-carbon composite material; the mass ratio of the metallic silicon precursor to the liquid aromatic halogenated hydrocarbon is 1:(1-20).
2. The method for preparing the silicon-carbon composite material according to claim 1, characterized in that: The alkaline earth metal is one or more of Mg, Ca, Sr and Ba, preferably Ca and / or Mg; And / or, the size of the silicon powder may be 10 nm-2 μm; and / or, the molar ratio of the alkaline earth metal to the silicon powder is 4:(1.5-8), preferably 4:(1.5-2), such as 4:1.8, 4:1.85, 4:1.9, 4:1.95 or 4:2; And / or, when the alkaline earth metals are Mg and Ca, the molar ratio of Mg:Ca:silicon powder is (1-4):1:(1.5-2), for example, 3:1:1.8, 3:1:1.9 or 3:1:
2.
3. The method for preparing the silicon-carbon composite material according to claim 1, characterized in that: The calcination temperature is 400-600°C, for example 500°C; And / or, the calcination time is 3-6 hours, such as 4 hours or 5 hours.
4. The method for preparing the silicon-carbon composite material according to claim 1, characterized in that: The chemical formula of the metal silicon precursor is Ca 4-x Mg x Si2, where 0≤x≤4, for example, x is 0.5, 1, 2 or 4; And / or, the mass ratio of the metal silicon precursor to the liquid aromatic halogenated hydrocarbon is 1:1, 1:2, 1:3, 1:5 or 1:10, preferably 1:(8-15).
5. The method for preparing the silicon-carbon composite material according to claim 1, characterized in that: The halogen in the liquid aromatic halogenated hydrocarbon is one or more of F, Cl, Br and I, such as Cl; and / or, the number of halogen atoms in the liquid aromatic halogenated hydrocarbon is 1-6, such as 1, 2 or 3; And / or, the liquid aromatic halogenated hydrocarbon is a liquid side-chain halogenated aromatic hydrocarbon and / or a liquid aromatic ring halogenated aromatic hydrocarbon.
6. The method for preparing the silicon-carbon composite material according to claim 5, characterized in that: The halogen in the liquid side-chain halogenated aromatic hydrocarbon is a halogenated aromatic hydrocarbon connected to the α position of the side chain, such as benzyl chloride; And / or, the liquid aromatic halogenated aromatic hydrocarbon is one or more of chlorobenzene, 2,6-dichlorotoluene, 1,2-dichlorobenzene and p-chlorotoluene.
7. The method for preparing the silicon-carbon composite material according to claim 1, characterized in that: The temperature of the solvothermal reaction does not exceed the boiling point of the liquid aromatic halogenated hydrocarbon, preferably 80-160°C, such as 85°C, 100°C, 120°C or 150°C; When the liquid aromatic halogenated hydrocarbon is chlorobenzene, the temperature of the solvent thermal reaction is preferably 80-120°C, such as 85°C or 120°C, more preferably 100-120°C; When the liquid aromatic halogenated hydrocarbon is 2,6-dichlorotoluene, the temperature of the solvent thermal reaction is preferably 100-160°C, such as 120°C or 150°C, more preferably 100-130°C; When the liquid aromatic halogenated hydrocarbon is benzyl chloride, the temperature of the solvothermal reaction is preferably 100-160°C, such as 120°C or 150°C, more preferably 100-130°C; And / or, the solvent thermal reaction time is 3-18 h, such as 5 h, 6 h, 8 h or 10 h, preferably 8-12 h.
8. A silicon-carbon composite material, characterized in that: The silicon-carbon composite material is prepared according to the method for preparing the silicon-carbon composite material as described in any one of claims 1 to 7.
9. Use of the silicon-carbon composite material as claimed in claim 8 in a lithium-ion battery.
10. An electrochemical device, characterized in that: It comprises a positive electrode, a negative electrode, an electrolyte and a separator, wherein the negative electrode comprises the silicon-carbon composite material as claimed in claim 8.
Citation Information
Patent Citations
Porous silicon particles and a method for producing silicon particles
CN107848809A
Titanium dioxide nanotube-loaded carbon-coated nano-silicon composite material as well as preparation method and application of titanium dioxide nanotube-loaded carbon-coated nano-silicon composite material
CN112563509A
Silicon-carbon composite material and preparation method thereof
CN115108556A
Three-dimensional porous carbon coated silica powder composite material, preparation method thereof and application of three-dimensional porous carbon coated silica powder composite material in lithium ion battery
CN115763767A
Production process for carbon-coated silicon material
US20170256793A1